2013
DOI: 10.1631/jzus.b1200263
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the oxidative stress mediates the cardioprotection of bicyclol against ischemia-reperfusion injury in rats

Abstract: Abstract:Objective: To investigate the beneficial effect of bicyclol on rat hearts subjected to ischemia-reperfusion (IR) injuries and its possible mechanism. Methods: Male Sprague-Dawley rats were intragastrically administered with bicyclol (25, 50 or 100 mg/(kg·d)) for 3 d. Myocardial IR was produced by occlusion of the coronary artery for 1 h and reperfusion for 3 h. Left ventricular hemodynamics was continuously monitored. At the end of reperfusion, myocardial infarct was measured by 2,3,5-triphenyltetrazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
0
5
0
2
Order By: Relevance
“…Using an established protocol, 28,33,34 single ventricular myocytes were prepared from adult rats by enzymatic dissociation. Briefly, the heart was perfused at 378C with 100% oxygenated, Ca 2+ -free Tyrode's solution, and then the solution was switched to 100% oxygenated, recirculating low-Ca 2+ Tyrode's containing 0.03% collagenase and 1% bovine serum albumin for 10 minutes.…”
Section: Isolation Of Rat Ventricular Myocytesmentioning
confidence: 99%
“…Using an established protocol, 28,33,34 single ventricular myocytes were prepared from adult rats by enzymatic dissociation. Briefly, the heart was perfused at 378C with 100% oxygenated, Ca 2+ -free Tyrode's solution, and then the solution was switched to 100% oxygenated, recirculating low-Ca 2+ Tyrode's containing 0.03% collagenase and 1% bovine serum albumin for 10 minutes.…”
Section: Isolation Of Rat Ventricular Myocytesmentioning
confidence: 99%
“…Протективный эффект Бициклола был доказан в работах in vitro и in vivo, моделирующих различные формы повреждения печени четыреххлористым углеродом, ацетаминофеном, D-галактозамином и конкавалином А. Бициклол угнетает продукцию фактора некроза опухоли активными нейтрофилами, купферовскими клетками и макрофагами, а также способствует уменьшению интенсивности свободнорадикального повреждения (рис. 1) [8][9][10][11][12][13][14][15][16][17][18].…”
Section: уровень алт и аст вызывающий повышение смертности комментарииunclassified
“…10,0 (7,(6)(7)(8)(9)(10)(11)(12)(13)0) 40-49 17,2 (11,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)2) 36, 3 (26,9-49,1) 50-99 46, 8 (36,5-59,9) 89,4 (71,9-111,2) >100 61, 6 (38,9-97,6) 178, 8 (115,5-254,9) Уровень АЛТ в сыворотке крови (ед/л) (5,(8)(9)9) 40-49 21,4 (15,2) 17,8 (13,2) 50-99 27,5 (20,9) 31,6 (25,0-40,0) >100 30,0 (16,9) 82, 8 (58,4-117,5) Примечание. Скорректировано по возрасту, индексу массы тела, курению, потреблению алкоголя, уровню глюкозы в плазме, уровню общего холестерина в сыворотке крови, артериальному давлению и семейному анамнезу заболевания печени.…”
Section: уровень алт и аст вызывающий повышение смертности комментарииunclassified
“…If mitochondria are protected, however, myocardial cell function can gradually recover to avoid causing irreversible damage (23). It has previously been suggested that mitochondrial calcium overload is an important contributory factor to myocardial injury during ischemia-reperfusion (24). Free and stable Ca 2+ regulation is necessary for ATP production in the mitochondria (25).…”
Section: A B C D Ementioning
confidence: 99%